2004
DOI: 10.1038/sj.emboj.7600218
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo role of PtdIns(3,4,5)P3 binding to PDK1 PH domain defined by knockin mutation

Abstract: We generated homozygous knockin ES cells expressing a form of 3-phosphoinositide-dependent protein kinase-1 (PDK1) with a mutation in its pleckstrin homology (PH) domain that abolishes phosphatidylinositol 3,4,5-tris-phosphate (PtdIns(3,4,5)P3) binding, without affecting catalytic activity. In the knockin cells, protein kinase B (PKB) was not activated by IGF1, whereas ribosomal S6 kinase (RSK) was activated normally, indicating that PtdIns(3,4,5)P3 binding to PDK1 is required for PKB but not RSK activation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 40 publications
9
135
0
Order By: Relevance
“…Phosphorylation of PKA T197 relative to total PKA was also slightly decreased in PDK1 −/− ES cells to PDK1 −/− +LG ES cells. Total levels of various PKC isoforms were also increased following expression of PDK1 L159G, consistent with previous reports [32]. We then analyzed phosphorylation of PDK1 substrates following incubation with the PP1 analogues 1-NM-PP1 and 3,4-DMB-PP1 in PDK1 −/− +LG cells.…”
Section: Phosphorylation Of Known and Potential Pdk1 Targets Followinsupporting
confidence: 87%
“…Phosphorylation of PKA T197 relative to total PKA was also slightly decreased in PDK1 −/− ES cells to PDK1 −/− +LG ES cells. Total levels of various PKC isoforms were also increased following expression of PDK1 L159G, consistent with previous reports [32]. We then analyzed phosphorylation of PDK1 substrates following incubation with the PP1 analogues 1-NM-PP1 and 3,4-DMB-PP1 in PDK1 −/− +LG cells.…”
Section: Phosphorylation Of Known and Potential Pdk1 Targets Followinsupporting
confidence: 87%
“…In the same studies, the total levels of PKC were reported to be relatively stable in ES cells lacking PDK-1 and phosphorylation at the A-loop was abolished [37,38]. In T lymphocytes, Ghosh and colleagues have demonstrated that knockdown of PDK-1 expression inhibits A-loop phosphorylation of PKC [39]; this defect is recapitulated in PDK-1-null T cells [40].…”
Section: Accepted M Manuscriptmentioning
confidence: 93%
“…PDK-1 has been shown to phosphorylate cPKC, nPKC and aPKCs both in vitro and when over-expressed in different cell types [33][34][35][36]. Most importantly perhaps is that the intracellular levels and/or A-loop phosphorylation of PKCs is [37,38].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the role of PDK1-Akt/mTOR pathway in liver regeneration, we employed the "pif-pocket" mutant of PDK1, which allows PDK1 to signal exclusively to Akt but not to p70 S6K or others. 30,[34][35][36] Adenovirus-mediated introduction of the pif-pocket mutant (L155E) did re-phosphorylate Akt (Thr308), but not p70 S6K (Thr389), 4 hours after PH in L-Pdk1KO mice (Fig. 5A).…”
Section: L-pdk1komentioning
confidence: 99%